Novel Potential Probiotic Lactobacilli for Prevention and Treatment of Vulvovaginal Infections - Kumherová, Monika; Veselá, Kristina; Kosová, Michaela; Mašata, Jaromír; Horáčková, Šárka; Šmidrkal, Jan (Probiotics and antimicrobial proteins, 2021)
Lactobacilli in the vaginal tract are essential to protect against microbial infections. We therefore focused on isolating vaginal lactobacilli from pregnant women and testing their functional properties. Lactobacilli were isolated from 50 vaginal swabs and the purified isolates were identified by MALDI-TOF MS. Functional properties (antimicrobial activity, organic acids and hydrogen peroxide production, antibiotic susceptibility, auto-aggregation, and hydrophobicity) of selected isolates were tested. Lactobacilli (41 strains) were identified in 58% of swabs with a predominance of Lactobacillus crispatus (48%) followed by L. jensenii (21%), L. rhamnosus (14%), L. fermentum (10%), and L. gasseri (7%). The highest antibacterial activity was determined for L. fermentum and L. rhamnosus. Strong anti-Candida activity was observed for strains L. crispatus, L. fermentum, and L. rhamnosus. Strain L. jensenii 58C possessed the highest production of hydrogen peroxide (6.32 ± 0.60 mg/l). The best lactic acid producer was strain L. rhamnosus 72A (11.6 ± 0.2 g/l). All strains were resistant to fluconazole and metronidazole. The highest auto-aggregation was observed for strain L. crispatus 51A (98.8 ± 0.1% after 24 h). Strain L. rhamnosus 68A showed the highest hydrophobicity (69.1 ± 1.4%). Strains L. fermentum and L. rhamnosus showed high antibacterial activity and hydrophobicity, and strains L. crispatus possessed high auto-aggregation and anti-Candida activity. Thus, these strains alone or in a mix could be used for the preparation of probiotic products for treatment and prevention of vulvovaginal infections of pregnant and non-pregnant women.
Keywords: vaginitida; Vagina; Humans; Female; Candida; Vulvitis; Probiotics; lidé; Lactobacilli; ženské pohlaví; těhotenství; Lactobacillus; Vaginal microbiome; Vaginitis; vagina; Candidiasis; vulvitida; dospělí; Pregnancy; Adult; kandidóza; Vulvovaginal infections